A new infra-specific taxon of Acalypha fimbriata Schum. & Thonn. from Nigeria (Bangladesh Journal of Plant Taxonomy, 2014)
This study shows that the populations of Acalypha fimbriata Schum. & Thonn. occurring in Nigeria are divisible into two recognizable varieties, viz., A. fimbriata Schum. & Thonn. var. fimbriata and A. fimbriata var. robusta Kadiri var. nov. Generally, the populations have a suite of similar characters in their vegetative and reproductive organs and the ultra-structures of the leaf cuticle using scanning electron microscope showed uniformity of characters like sunken stomata, wide-narrow stomatal opening and conspicuous periclinal wall. However, the two varieties are discriminated based on 1 vs. 2 fruits per bract, slim vs. robust stature, scanty vs. clumsy inflorescence on the axillary spike, leaf apex character as well as smooth and rough unicellular trichomes. The observation is supported by a T-test at 95% similarity confidence while the 14 populations consisting of 280 individuals used for the analysis are separated into two by the scatter diagram. Neighbour joining analysis using Euclidean measure and UPGMA dendrogram reveal the level of relationships. Therefore, one of the varieties is based on the description of the earlier described type specimen and the other variety being different is considered as a new taxon Acalypha fimbriata var. robusta Kadiri.DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19265Bangladesh J. Plant Taxon. 21(1): 53-62, 2014 (June)